Challenges to Improve Bone Healing Under Diabetic Conditions - Chen, Yiling; Zhou, Yue; Lin, Jie; Zhang, Shiwen (Frontiers in Endocrinology, 2022)
Diabetes mellitus can affect bone metabolism and the bone microenvironment, resulting in impaired bone healing. The mechanisms include oxidative stress, inflammation, the production of advanced glycation end products (AGEs), etc. Improving bone healing in diabetic patients has important clinical significance in promoting fracture healing and improving bone integration. In this paper, we reviewed the methods of improving bone healing under diabetic conditions, including drug therapy, biochemical cues, hyperbaric oxygen, ultrasound, laser and pulsed electromagnetic fields. Meanwhile, we also pointed out some shortcomings and challenges, hoping to provide a potential therapeutic strategy for accelerating bone healing in patients with diabetes.